Remember Order of Operations
PEMDAS
Number One
-12 + -6 -9 = -27
Number Two
-13-7+-2- -8
Where the two negatives are, you must multiply those two negatives to get a plus
-13-7-2+8 = -14
2006-10-28 14:55:46
·
answer #1
·
answered by Bentnalboy 3
·
1⤊
0⤋
Answer 1:
-12 + -6 - 9 = -12-6-9
= -(12 + 6 + 9)
= -27
Answer 2:
-13 - 7 + -2 - -8 = -13-7-2 + 8
= -(13 + 7 + 2 -8)
= - 14
2006-10-28 22:59:29
·
answer #2
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
0⤋
-12 + (-6) - 9 = -12 - 6 - 9 = -(12 + 6 + 9) = -27
-13 - 7 + (-2) - (-8) = -13 - 7 - 2 + 8 = 8 - (13 + 7 + 2) = 8 - 22 = -14
2006-10-28 21:57:49
·
answer #3
·
answered by Anonymous
·
2⤊
0⤋
-12 - 6 + -9= -27
-13 - 7 +-2- - 8= -14
2006-10-28 21:58:26
·
answer #4
·
answered by Anonymous
·
1⤊
0⤋
two negatives side by side equals a positive.
-12 -6 = -18-9= -27
-13-7= -20-2=-22+8= -14
2006-10-28 21:58:22
·
answer #5
·
answered by Aaron 3
·
1⤊
0⤋
they are all like sign . the sum of -6 and -9 is -15.
-12 + (-15)=-27
the sum of -13 and -7 is -20.
the difference of -2 and 8 is +6.
so -20+(+6) = -14
2006-10-29 04:34:08
·
answer #6
·
answered by the walking brother 2
·
0⤊
0⤋
-12+6 - 9 = -3
-13 - 7 + -2 - 8= -30
amen and god bless you too
2006-10-28 21:57:28
·
answer #7
·
answered by Anonymous
·
0⤊
2⤋
I don't really understand why always giving the same answer to a particular sum is wrong ... if it's the right answer why would it change?
My answers would always be -27 and -14 (if they were in base 10 and what I consider to be a normal number space, not something that wraps around on a ring or anything weird).
2006-10-28 21:58:58
·
answer #8
·
answered by Anonymous
·
1⤊
0⤋
-12+-6-9
-12+-15
-27
-13-7+-2- -8
-13-7+-2+8
-20+6
-14
I hope this helps!
2006-10-28 22:22:05
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
-12 +(-6) - 9 =
- 12 - 6 - 9 =
- 27
The answer is - 27
- - - - - - - - - -
- 13 - 7 + (-2) - (- 8)
-20 - 2 + 8
- 22 + 8
- 14
The answer is - 14
- - - - - -s-
2006-10-29 04:10:21
·
answer #10
·
answered by SAMUEL D 7
·
0⤊
0⤋